Pelatihan Pembukuan Sederhana bagi Pelaku UMKM - Monalika, Hani Putri (Jurnal Pemberdayaan Umat, 2025)
Purpose: This training aims to increase knowledge and understanding for MSME actors in learning simple bookkeeping for their business activities. Methodology/approach: The method of this community service activity is to deliver material using seminar methods and limited discussions related to accounting material. Result/findings: Based on the results of a face-to-face survey of MSMEs, the spread of COVID-19 has had a direct impact on the decline in their economic income. Several policies require everyone to maintain social distancing, children are on school holidays, and even home lockdowns. This has undoubtedly impacted the sales of some MSMEs, especially those selling daily necessities. Inventory of merchandise is also damaged and cannot be resold because it has expired. Conclusions: 1) Bookkeeping systems, accounting cycles, and financial reports. 2) Partners are unable to prepare bookkeeping documents and record them in detail and neatly according to the accounting cycle. 3) Partners are unable to calculate profits in preparing financial reports according to the accounting cycle. 4) Marketing. Business actors lack understanding in selecting and determining market segments and market needs in their surrounding environment. Limitations: This research only focuses on training related to simple bookkeeping of financial reports for MSME actors, other factors such as financial management, promotion, and others are not discussed further in this research. Contributions: It is hoped that this training will enhance MSMEs' knowledge of financial reporting and increase their confidence in interacting with third parties, such as lending institutions and investors. It will also encourage investors to invest in this sector.